In situ growth of carbon nanotubes on fly ash substrates - Liu Song; Wang Tianhao; Wang Hongchang; Hui David; Li Haitao; Gong Minghui; Cai Bianyue; Zhang Duanyang; Xu Kechun; Tang Aoyu (Nanotechnology Reviews)
Carbon nanotubes (CNTs) are one-dimensional nanomaterials exhibiting specialized structures and exceptional mechanical, electrical, and chemical properties. CNTs find application in the fabrication of composite materials, material modification, and hydrogen storage. However, their widespread adoption in material modification is challenging due to their expensive manufacturing and proclivity toward agglomeration. This review expounds the evolution and future directions of in situ growth of CNTs on fly ash substrates through chemical vapor deposition or microwave heating methods. The unique structure and composition of fly ash engenders low-carbon and environmentally friendly properties while facilitating the self-growth of CNTs on its substrate. This paper delves into the characteristics and growth mechanism of the in situ-grown CNTs, with an analysis of mechanical properties, wave absorption, friction, applications, and innovations of fly ash in situ-grown CNTs as modifiers, adsorbents, and additives. The prepared fly ash in situ-grown CNTs have various advantages such as better dispersion properties, lower carbon emissions, and reduced preparation cost, enhancing their applicability in material modification and creation.